Elaboração e avaliação de um programa de intervenção psicopedagógico para orientação de pais de crianças com dificuldades de aprendizagem PPOP - Rolfsen, Andréia Bevilacqua (Universidade Federal de São Carlos, 2008)
Admission at the elementary school is an important moment in the process of education. Literature has shown that to guide the family in this process, using resources from the family environment, may be fundamental in preventing school problems. In that context, this work implemented and evaluated a proposal of intervention in the form of a Programa Psicopedagógico de Orientação a Pais (PPOP) - Psychopedagogical Program of Parents Orientation -, for the parents and relatives responsible for children with learning disabilities included in the early years of elementary grades of regular public school and were attended by the itinerant service of special education, in order to provide strategies for monitoring and stimulation of their children in that stage of education. The study was developed as the ethical aspects of researches that involve human beings. The first stage of the research (Program s elaboration) tested the PPOP and the instruments in an experimental situation, whose analysis showed that the Program was able to be implemented on a larger scale and was satisfactory as the form and content, from the reports of the participants. The used instruments also were sensitive to the demand for collection. On the second stage, the implementation of the Program, participated in this research eleven parents of students who were on the early years at public elementary school and their respective children, which composed two groups experimental and control). It is relevant to mention that the content approached in the program is based on the book Como ajudar seu filho na escola ( How to help your child in school ). Besides the PPOP, the instruments used to collect data were: Home Environment Resources Scale - HERS, Roadmap, interviews with parents, Brazil s Criterion of Economic Classification, School Achievement Test, Roadmap " Situations and the Evaluation Questionnaire Course. The evaluation of the program found the effectiveness of it, from the assessment of all the steps and comparison of results of pre - and post-tests. The results allowed to assert the need for continuation of activities of that nature. The results allowed to assert the need for continuation of activities of that nature. The results showed: a) interest of mothers receive support in situations where information about the "do not know how to deal with the child" b) an increase in the repertoire of mothers of educational practices appropriate c) implementation of positive strategies on a daily basis with the children in the short term; d) the relevance of programs of this nature with parents of children with learning disability. In future studies it is suggested investment in training of ducators to use the POPP and development of strategies that extend the benefits of the program to more families.
Keywords: Programa de intervenção; Psicopedagogia; Educação especial inclusão; Prevenção; Dificuldades de aprendizagem; Relação família-escola; Inclusion; Prevention; Learning disabilities; Intervention programs; Family; School; Bio-Ecological systems theory; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL